Scientific Document Review at the Centers for Disease Control and Prevention: The CLEAR Approach - Iskander, John K.; Calugar, Angela; Peavy, Richard D.; Sowell, Anne (American journal of public health (1971), 2017)
Scientists at the US Centers for Disease Control and Prevention (CDC) publish an average of 50 peer-reviewed articles per week,1 in addition to numerous other widely disseminated materials. Even non-subject matter reviewers should be able to assess whether the authors are clearly describing study methods, including case definitions and inclusion or exclusion criteria, and whether inferences drawn are reasonable and discussion of contradictory or inconsistent results is adequate. 3.Ethics considerations include not only acknowledgment of institutional review board or other human participant protection review, but also whether readers may perceive broader ethical concerns. Relevance may refer to increased awareness or recommended actions related to emerging conditions and their risk factors, use of new diagnostic criteria or laboratory tests, or reporting of specific conditions to public health authorities. Any MMWR content considered to be human participant research must describe review by the institutional review board and, when appropriate, clinical trial registration (E). Because articles published in MMWR represent agency policy,4 reviewers assess whether policy-related statements are consistent with CDC policy or recommendations (A). During public health emergency responses, when rapid review and dissemination of evolving information are critical, this system is especially valuable.6 Best practices for reviewers include providing comments that are specific and actionable and making clear the distinction between mandatory (level 1) and voluntary (levels 2 and 3) comments. The CLEAR framework, which can be applied to both internal and peer review processes conducted in a variety of public health settings, has the potential to increase the speed with...